A biodegradable and edible packaging film based on papaya puree, gelatin, and defatted soy protein. (December 2016) - Tulamandi, Sreedath; Rangarajan, Visvanathan; Rizvi, Syed S.H.; Singhal, Rekha S.; Chattopadhyay, Sanjay Kr.; Saha, Narayana Chandra
Graphical abstract: Highlights: Water solubility has lower with the addition of defatted soy protein in the edible films. Optical properties are as much comparable with the polymer based packaging materials. Higher seal strength and tear strength indicated the usage of edible films to practical packaging processes. Abstract: Study of physical and mechanical properties of edible films produced out of various blends of papaya puree (PP), gelatin (G) and defatted soy protein (DSP). Film forming solutions at different levels of papaya puree, gelatin and defatted soy protein were prepared and the films were cast at room temperature. The results of this study indicated, with the addition of gelatin to the papaya puree, the films had shown significant increase (P < 0.05) in color properties, tensile strength and seal strength. Whereas, with the addition of defatted soy protein along with gelatin to the papaya puree, the films had shown significant increase (P < 0.05) in elongation, water permeability, water contact angle and decrease in water solubility. In addition, differential scanning calorimetric (DSC) analysis indicated higher transition, melting temperature and enthalpy in papaya puree blended films (PP/4DSP/3G) (Tg  = 121.81 ± 0.20 a  °C, Tm  = 174.59 ± 0.52 a   ° C and ΔH = 220.76 ± 0.36 a  J/g). The analysis of blended papaya films by fourier transforms infrared spectra revealed significant compatibility of papaya puree, gelatin and defatted soy protein and their influence on optical, mechanical, barrier and structural properties. Thus, based on these observations, the papaya blended films could be effectively used as primary packaging material in near future.